2014
DOI: 10.1103/physreva.90.042712
|View full text |Cite
|
Sign up to set email alerts
|

Ion-momentum imaging of dissociative-electron-attachment dynamics in acetylene

Abstract: We present experimental results for dissociative electron attachment to acetylene near the 3 eV 2 Π g resonance. In particular, we use an ion-momentum imaging technique to investigate the dissociation channel leading to C 2 H − fragments. From our measured ion-momentum results we extract fragment kinetic energy and angular distributions. We directly observe a significant dissociation bending dynamic associated with the formation of the transitory negative ion. In modeling this bending dynamic with ab initio el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This is to be expected, since our structure calculations show that there is a significant energy barrier to direct dissociation. When axial recoil breaks down, we can still use the computed entrance amplitudes to predict angular distributions when we have theoretical evidence that points to how the recoil axis rotates following electron attachment, as we have shown in several previous studies [2,4,6]. Our structure calculations show that by holding H-N-H fixed and rotating the third N-H in the direction away from H-N-H, the energy at the top of the barrier drops, becoming equal to the initial resonance energy at ∼25 degrees rotation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is to be expected, since our structure calculations show that there is a significant energy barrier to direct dissociation. When axial recoil breaks down, we can still use the computed entrance amplitudes to predict angular distributions when we have theoretical evidence that points to how the recoil axis rotates following electron attachment, as we have shown in several previous studies [2,4,6]. Our structure calculations show that by holding H-N-H fixed and rotating the third N-H in the direction away from H-N-H, the energy at the top of the barrier drops, becoming equal to the initial resonance energy at ∼25 degrees rotation.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics associated with these dissociative processes can be complex, involving conical intersections between different anion states and multiple fragment ion product channels [1][2][3][4]. The laboratory frame angular distributions of fragment ions can provide a unique insight into understanding the breakup process since they often contain signatures of the symmetry of the resonance state and are a key ingredient in unraveling the underlying dynamics of DEA [4][5][6]. In favorable cases where the dissociation is prompt, we have shown that the theoretically obtained electron entrance amplitude, which ties the molecular-to the laboratory-frame, can be used to predict laboratoryframe angular distributions and identify specific dissociation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the bond-cleavage drops with the increasing distance (alkyl chains length) between the π* system and the dissociating bond . It also leads to puzzling temperature effects and angular distributions. , The effect demonstrated here, coupling induced by motion of a distant molecular part, has been suggested, ,, but this is its first experimental evidence. However, all the prior works assumed that π* states couple to repulsive shape resonances.…”
mentioning
confidence: 68%
“…[2][3][4][5] In the favorable case of prompt dissociation, characterized by the existence of predominant dissociation pathways, electronmolecule scattering calculations can tie the observed angular distributions to specific dissociation mechanisms, as shown recently in DEA to methanol 6 and acetylene. 7 Methane is a candidate of considerable interest for a detailed investigation of DEA, not only for its importance in planetary atmospheres and technological plasmas, but also because its dissociation mechanisms remain something of a mystery. The recent experimental study of Ram and Krishnakumar 8 revealed a high-level of complexity in the DEA mechanism of methane.…”
Section: Introductionmentioning
confidence: 99%